3d-9-8b=11

Simple and best practice solution for 3d-9-8b=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3d-9-8b=11 equation:


Simplifying
3d + -9 + -8b = 11

Reorder the terms:
-9 + -8b + 3d = 11

Solving
-9 + -8b + 3d = 11

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + -8b + 9 + 3d = 11 + 9

Reorder the terms:
-9 + 9 + -8b + 3d = 11 + 9

Combine like terms: -9 + 9 = 0
0 + -8b + 3d = 11 + 9
-8b + 3d = 11 + 9

Combine like terms: 11 + 9 = 20
-8b + 3d = 20

Add '-3d' to each side of the equation.
-8b + 3d + -3d = 20 + -3d

Combine like terms: 3d + -3d = 0
-8b + 0 = 20 + -3d
-8b = 20 + -3d

Divide each side by '-8'.
b = -2.5 + 0.375d

Simplifying
b = -2.5 + 0.375d

See similar equations:

| x^2+7x-1=7 | | n^4-13n^2+36=0 | | 5g*4d= | | 11-8x=0 | | x^2+10x-27=8x-3 | | 5x-33=2x+57 | | =0.4(3d-5) | | -2y+3(-2)+5y+35=6y+2(-2)-3y+8 | | 2x+9y=4 | | 2(-2)-3+5y+6=8y-4(-2)+24 | | 3x+7y=6 | | 9(x-2)-4=14 | | -9x+3+5x=2x-3x+3+7-2 | | -x-2y+z=-6 | | 3x/7-5=4 | | 9(x-1)+3x=-9x+5 | | 2x+4y-2z=6 | | 0.42x-5=4 | | x+3y-z=12 | | 5x-y+5z=30 | | 5x-2x+6-4+14=5x-3x+8 | | 3(g-7)-2=4 | | 16=-4-4x | | -x+2y-3z=-9 | | -3t+5=26 | | 4x-2x+3-8=7x-5+4x | | 3t+5=26 | | (x^2+y^4)(x^2-y^4)=0 | | 0.67x+7=21 | | 72+36=0 | | 5x-2+8=7x-4 | | 21=8x-75 |

Equations solver categories